2018
DOI: 10.3390/su10061706
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Knowledge Economy and Global Competitiveness in the European Union

Abstract: The main purpose of this paper is to study the influence of various indicators related to the knowledge economy on country competitiveness in the European Union (EU). Based on the Pearson coefficient and panel-data regression models, we analyzed the Global Competitiveness Index (GCI) in relation to research and development (R&D) expenditure (as a % of gross domestic product (GDP)), percentage of population with tertiary education, lifelong learning, GDP per capita, and debt to equity. The findings highlighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 31 publications
6
78
0
1
Order By: Relevance
“…Literature often regards vis-à-vis knowledge how significant role it has in competitiveness of developing countries. (Dima et al, 2018) Indeed, this makes it possible for these countries to appear in markets outside their borders. It is also worth mentioning that we hardly meet a developing country on this developmental path.…”
Section: Theory and Questionsmentioning
confidence: 99%
“…Literature often regards vis-à-vis knowledge how significant role it has in competitiveness of developing countries. (Dima et al, 2018) Indeed, this makes it possible for these countries to appear in markets outside their borders. It is also worth mentioning that we hardly meet a developing country on this developmental path.…”
Section: Theory and Questionsmentioning
confidence: 99%
“…Increasing investments in research and the introduction of new products improve the living condition of the population and lead to developments in both the public and private sectors. Dima et al (2018) investigated the impacts of knowledge economy on country competitiveness in the European Union by using Perason coefficient and panel-data regression models. The findings show the key role of innovation and education as main determinants of European Union economic convergence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, their relationship cannot be considered isolated from macroeconomic stability that an economy shows. Moreover, business sophistication, which would refer to the quality of business networks and the quality of businesses' operations and strategies, is one of the triggers that foster economic growth through improving efficiency, productivity, and profitability in the market (Dima, Begu, Vasilescu, & Maassen, 2018). Existing academic researchers in the literature have mainly focused on analysing firm or sector level data to discern an explanation for business innovation, research and development activities, along with the firm or sector level growth (Tsuji, Ueki, Shigeno, Idota, & Bunno, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Strong evidence that knowledge should integrate innovation is labor (Guo et al, 2019), in which the authors, after analyzing data from 295 entrepreneurs and top managers in Chinese high-tech new businesses, found that both the coherent integration of knowledge and the system integration of knowledge have a positive effect on high-tech productivity and innovation activity. The study of the impact of various indicators related to knowledge economy on the country's competitiveness in the European Union (EU) became the subject of a study by Dima et al (2018). It was determined that the development of EU policies on learning opportunities throughout the life of the European workforce and focusing on research and development can significantly contribute to the competitiveness of EU Member States.…”
Section: Literature Reviewmentioning
confidence: 99%